cEBP Homologous Protein Expression in Macrophages Regulates the Magnitude and Duration of IL-6 Expression and Dextran Sodium Sulfate Colitis - Datta, Shyamasree (J Interferon Cytokine Res, 2015)
Cellular stress enhances inflammatory cytokine gene expression by inducing cEBP homologous protein (CHOP). Engaging cell stress via thapsigargin induced CHOP and selectively prolonged lipopolysaccharide-stimulated interleukin-6 (IL-6) expression in bone marrow-derived macrophages from wild-type (WT) but not CHOP knockout (KO) mice. To determine the impact of this mechanism in vivo we employed dextran sodium sulfate (DSS)-induced colitis in irradiated mice reconstituted with bone marrow from WT or CHOP KO mice. WT recipients of CHOP KO bone marrow exhibited more rapid recovery from disease than did mice reconstituted with WT bone marrow as reflected in increased survival, reduced clinical scores, and colonic histopathology. No differences in mesenteric lymph node cell populations were observed between mice with WT or CHOP KO bone marrow during colitis. CD11b(+) macrophages infiltrating the lamina propria were, however, reduced in DSS-treated mice reconstituted with CHOP KO bone marrow. CHOP expression was observed within the infiltrating inflammatory CD11b(+) macrophages. Furthermore, IL-6 expression within the inflamed colon was significantly lower in mice with CHOP-deficient bone marrow. Our findings indicate that CHOP expression in myeloid cells plays an important role in determining the magnitude and duration of inflammatory response in vivo by modulating expression of proinflammatory cytokines such as IL-6 in infiltrating macrophages.